ANALISIS PENGARUH INFORMASI KEUANGAN DAN UKURAN DEWAN TERHADAP UNDERPRICING DENGAN VARIABEL KONTROL UKURAN PERUSAHAAN (Studi Kasus pada Perusahaan yang Melakukan IPO di BEI Periode 2010-2015) - Syafira, Vina Febria; Kamal, Mustofa (Diponegoro Journal of Management, 2016)
Companies need substantial capital to maintain the companies’ existence and they often choose capital market as a medium to increase the capital, but companies often experience underpricing when they do initial public offering. Underpricing phenomenon occurs when there is a positive difference between the closing price in the secondary market on the first day and the IPO price. This study aims to determine the effect of financial information (leverage, EPS, and ROA) and board size on the level of underpricing in companies that did Initial Public Offering in Indonesia Stock Exchange during 2010-2015. The samples used in this study were 86 companies who did initial public offering in Indonesia Stock Exchange during 2010-2015 and experienced underpricing. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that EPS has a positive significant effect on underpricing, ROA has a negative significant effect on underpricing, while leverage, board size, and firm size have insignificant effect on underpricing.